The Impact Of Board Characteristics And Internal Audit Effectiveness On Bank Performance In The Kingdom Of Saudi Arabia: Environmental Disclosure As A Moderator - Mustafa, Alshorman Emran Ali (2024)
The Current Study Endeavors To Assess The Influence Of Board Characteristics And Internal Audit Effectiveness On The Performance Of Banks In Saudi Arabia, With A Specific Focus On The Moderating Role Of Environmental Disclosure. The Sample Of The Study Consists Of 21 Banks, 12 Of Which Are Domestic Commercial Banks And 9 Of Which Are Foreign Commercial Banks. In Addition, The Collected Data From Published Annual Reports Covered The Five Financial Years 2016 To 2020. Employing A Quantitative Methodology, The Study Analyzes Data Extracted From The Annual Reports Of Select Saudi Arabian Banks. Through The Application Of Statistical Methods Such As Descriptive Statistics And Linear Regression Models, The Research Uncovers Significant Insights Notably, The Findings Underscore The Substantial Impact Of Board Size And The Frequency Of Board Meetings On Return On Assets. Furthermore, Internal Audit Effectiveness Emerges As A Crucial Determinant Of Bank Performance. Importantly, The Study Reveals That Environmental Disclosure Plays A Pivotal Role In Moderating The Relationships Between Board Dynamics, Internal Audit Efficacy, And Bank Performance.